2021
DOI: 10.4103/ajm.ajm_200_20
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular lithotripsy to treat an underexpanded coronary stent during index procedure: A case report study

Abstract: Management of heavily calcified lesions during percutaneous coronary intervention (PCI) is often associated with high incidence of complications and long-term adverse outcomes. There is growing evidence of the efficacy of intravascular lithotripsy (IVL) in de novo coronary lesion preparation; however, little experience has been documented within freshly deployed stent underexpansion. We report a 66-year-old male with a marked stent underexpansion despite extensive lesion preparation due to severe underlying ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
5
0
4
Order By: Relevance
“…The mechanical energy from IVL is distributed uniformly across the inflated balloon into both superficial and deeper layers of the vessel, addressing calcium irrespective of circumferential location and depth [ 58 , 59 ]. Lastly, clinical experience has shown that IVL may also be used to modify calcium in ISR or underexpanded stents implanted in severely calcified lesions [ 60 , 61 , 62 , 63 ], including freshly deployed stents [ 64 ]. Moreover, IVL may be used as an adjunct to other atherectomy techniques when there has been inadequate calcium modification [ 65 ].…”
Section: Modalities For Coronary Calcium Modificationmentioning
confidence: 99%
“…The mechanical energy from IVL is distributed uniformly across the inflated balloon into both superficial and deeper layers of the vessel, addressing calcium irrespective of circumferential location and depth [ 58 , 59 ]. Lastly, clinical experience has shown that IVL may also be used to modify calcium in ISR or underexpanded stents implanted in severely calcified lesions [ 60 , 61 , 62 , 63 ], including freshly deployed stents [ 64 ]. Moreover, IVL may be used as an adjunct to other atherectomy techniques when there has been inadequate calcium modification [ 65 ].…”
Section: Modalities For Coronary Calcium Modificationmentioning
confidence: 99%
“…Kristian Rivera*, Diego Fernández-Rodríguez, Marta Zielonka, Ignacio Barriuso, Núria Pueyo-Balsells y Juan Casanova-Sandoval 1 Departamento de Cardiología, Hospital Universitari Arnau de Vilanova, Institut De Recerca Biomèdica de Lleida (IRBLLEIDA). Lleida, España.…”
Section: Intracoronary Lithotripsy As Bail-out Treatment Of An Undere...unclassified
“…La IS incrementa el riesgo de trombosis-reestenosis, de ahí la importancia de su tratamiento, con opciones limitadas. La aterectomía láser presenta problemas logísticos y pocos centros disponen de ella [1][2][3] . A: imagen con StentBoost (Philips Medical Systems ® , Eindoven, Países Bajos) que muestra la infraexpansión distal del stent (asterisco).…”
Section: Imágenes En Cardiologíaunclassified
See 1 more Smart Citation
“…Clinical registry and case series have recently been published, which showed the effectiveness and safety of S‐IVL to improve refractory stent under‐expansion. 10 , 11 , 12 , 13 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%